Censorship detected in LB (Lebanon) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Lebanon. Data sourced from OONI.
Censorship Incident ID: LB-2026-1148. Severity: critical. Confidence: 90%